Supporting Guatemalan Comadronas. Issue 5 (September 2021) - Callister, Lynn Clark
Abstract : The WHO Global Strategic Directions for Nursing and Midwifery was published by the World Health Organization for review April 1, 2021, with comments invited. It focuses on four strategic directions for nurses and midwives around the world: education, leadership, jobs, and service delivery. Our global health and nursing expert, Dr. Callister, explains the World Health Organization's strategic plans in the context of an ongoing program in Guatemala that is supporting village midwives.